Acoustical behavior of camellia sinensis/ananas comosus fiber based uni-directional corrugated panel for sound damping application - N Karthi; S Gokulkumar; S Sathish; U S Rajkumar (Materials Research Express, 2022)
To achieve a durable, rigid, and lightweight construction material, a new class of Camellia sinensis / Ananas comosus fiber-enhanced corrugated sandwich panel was designed and produced. The crushed core layer comprises sinusoidal corrugation and is manufactured by a method of mould pressing in an attempt to assess this material’s sound absorption ability. In addition, the influence of airgap and micro perforation on sound absorption properties was investigated. The samples with a greater perforation ratio and air gap are found to have a noise reduction coefficient (NRC) of 0.745, which can be used to attenuate mid- and high-range frequencies in industrial environments.